What Makes a Lesbian Salsa Space Comfortable? Reconceptualising Safety and Homophobia - Boulila, Stefanie Claudine (Lesbian Geographies: Gender, place and power, 2015)
This chapter explores the sexual spatialisation of salsa dance spaces through the narratives of lesbian salsa dancers. It draws on conversations with seven
Keywords: Bibliographie; Nettoyer

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity